Exploring Relationships and Inference Methods for Moments of Dual Generalized Order Statistics Derived from the Siddiqui-Dwivedi Distribution - Nayabuddin; Raghav, Yashpal Singh; Sabo, Shamsuddeen (Brazilian Journal of Biometrics, 2025)
In this paper, recurrence relation for single and product moments of dual generalized order statistics (DGOS) from Siddiqui-Dwivedi (SD) distribution are obtained. Furthermore, we provide the minimum variance linear unbiased estimator (MVLUE) of the position and scale parameters of the kth lower record values (LVR) and order statistics (OS) for the distribution under consideration. In the section 4, a characterization result is presented.